Phenotypic expression and challenges of a distinct form of thyrotoxicosis: Triiodothyronine-predominant Graves disease - Aggressive, refractory, and anything but banal - Dalan R. (Lippincott Williams & Wilkins, Inc., 2020)
10.1097/TEN.0b013e3181693d5e